Closed-loop ARS mode for scanning ion conductance microscopy with improved speed and stability for live cell imaging applications - Jung, Goo-Eun (2016)
Scanning ion conductance microscopy (SICM) is an increasingly useful nanotechnology tool for non-contact, high resolution imaging of live biological specimens such as cellular membranes. In particular, approach-retract-scanning (ARS) mode enables fast probing of delicate biological structures by rapid and repeated approach/retraction of a nano-pipette tip. For optimal performance, accurate control of the tip position is a critical issue. Herein, we present a novel closed-loop control strategy for the ARS mode that achieves higher operating speeds with increased stability. The algorithm differs from that of most conventional (i.e., constant velocity) approach schemes as it includes a deceleration phase near the sample surface, which is intended to minimize the possibility of contact with the surface. Analysis of the ion current and tip position demonstrates that the new mode is able to operate at approach speeds of up to 250 μm s−1. As a result of the improved stability, SICM imaging with the new approach scheme enables significantly improved, high resolution imaging of subtle features of fixed and live cells (e.g., filamentous structures & membrane edges). Taken together, the results suggest that optimization of the tip approach speed can substantially improve SICM imaging performance, further enabling SICM to become widely adopted as a general and versatile research tool for biological studies at the nanoscale level.